(3eMGVQGJ aj ebjGS bGfhf GdVQGFH (B/ s - (3OhOGM, QVhGfs; (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs ((3GdLRGFQs (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs, 2021)
(3eaGgje YGeI Mhd GdbGfhf GdVQjHj, GdefGRYGJ GdVQjHjI, GdZT h GdJgQH GdVQjHj(B.s
(3eQGLY U(B.101 s
Keywords: (3GdVQGFHs; (3bGfhf GdVQGFHs